Burnout, decision-making and coping among healthcare workers: How the world was before the COVID-19 pandemic - Amelia RIZZO; Rossella ALFA; Viviana CARLOTTA; Giuseppe STURNIOLO; Luigi TRAZZI; Francesco VIOLA (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: The international literature in the past two years has focused on work-related stress and burnout symptoms among healthcare workers involved in the COVID-19 emergency. However, high levels of burnout syndrome (BOS) had previously been traced in this population. The present study investigated the relationship between BOS, decision-making and coping styles in a sample of physicians and nurses before the pandemic. Methods: A sample of 90 healthcare workers (male= 47.9%; mean age = 45.23 ± 7.37) participated in the study. A socio-demographic questionnaire, the Link Burnout Questionnaire, the CISS Coping Inventory in Stressful Situations for adults and the General Decision-Making Style questionnaire were used. Results: Linear regression analysis showed that low decision style and emotion-oriented coping predict the onset of BOS. Subjects with and without BOS differ in decision-making styles and coping strategies. Discussion: This study could contribute to identifying precursors of BOS and suggests the need for preventive psychological and psychotherapeutic interventions to include emotions in the decision-making process.